ISSUES THAT NEED TO BE CHANGED IN THE LEGISLATION TO IMPROVE THE TAXATION OF BUSINESS ENTITIES (Scientific Conference on Multidisciplinary Studies, 2025)
This article analyzes some problematic aspects of the current legislation in improving the taxation system of business entities in the Republic of Uzbekistan and develops proposals for their elimination. The main attention in the study is paid to the need for the stability of tax legislation, further improvement of simplified tax regimes, legal strengthening of digital tax administration, and the introduction of a system for assessing the effectiveness of tax benefits.